Brand Consciousness, Social Comparison and Materialism amongst Teenagers - Waqar, Aqsa; Javed, Zainab; Rasool, Atif (Pakistan Journal of Humanities and Social Sciences, 2023)
The primary goal of the present study was to examine brand consciousness, social comparison, and materialism among teenagers. three instruments are used. (1) Consumer style inventory by Sporel & Kendall (1986), (2) social comparison orientation developed by Gibbons & Buunk (1999), and (3) Materialism scale: developed by Richins and Dawson (1992). The sample of the current study contains (N=200). SPSS was used for the analysis of data. Descriptive statistics will be calculated to assess the mean, standard deviation, and frequencies of the variable. Pearson product-moment correlation will use to find the relationship between Brand Consciousness, Social Comparison, and Materialism. Hierarchal Regression analysis will be used to find out the prediction. There is a statistically significant positive relationship between Brand Consciousness and Materialism. There is a significant positive relationship between social comparison and materialism. Brand Consciousness positively predicts materialism in teenagers. And social comparison positively predicts materialism amongst teenagers. The study will be beneficial to understand Brand Consciousness, Social Comparison, and Materialism, this study will guide us on how we improved our life without materialistic or branded products. This study will help psychologists to make social intervention techniques for helping people using social comparison in a worthy way.